Development of the theory of state regulation of innovation activity - Mekhovich, E. S.; Mekhovich, K. S.; Vorvul, A. S.; Vorvul, Yu. V.; Dyakova, N. M.; Pererva, P. G. (Луцький національний технічний університет, 2022)
It is proven that the state carries out all types of regulation of innovative activity - organizational, economic, financial, normative and legal. The state creates organizational, economic and legal conditions for innovative activity.
Розвиток теорії державного регулювання інноваційної діяльності
Keywords: innovative activity; state regulation; theory; methodology; practice